2014
DOI: 10.5539/ass.v10n22p17
|View full text |Cite
|
Sign up to set email alerts
|

Model Confirmation through Qualitative Research: Social Support System toward Entrepreneurial Desire

Abstract: Entrepreneurial world is trying their best level to attract university graduates across the world. Indonesian culture is still very colonial view that the status of employment is more respectable than being an entrepreneur. In addition, people often perceive that a university degree is much better and more important than a person's ability or skill. In fact, the skill is very much needed to support a person's life economically, instead of looking for a university degree first then searching the skill or capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Social Support: Much of the literature on entrepreneurship refers to social support as a potential entrepreneur's beliefs and expectations about the assistance and advice that he/she may receive from his/her social groups (Rani, 2012;Sahban, Kumar, & Sri Ramalu, 2014). These social groups include primary groups, such as parents, siblings,and spouse; and secondary groups, such as reference groups, comprising friends, colleagues and teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social Support: Much of the literature on entrepreneurship refers to social support as a potential entrepreneur's beliefs and expectations about the assistance and advice that he/she may receive from his/her social groups (Rani, 2012;Sahban, Kumar, & Sri Ramalu, 2014). These social groups include primary groups, such as parents, siblings,and spouse; and secondary groups, such as reference groups, comprising friends, colleagues and teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perceived support comes from the social context that female undergraduate students can avail, in the present case in landscape (Zhao, et al, 2005). Scholars detected that apart from psychological attributes and inclinations of individuals, skills, abilities, and social context also influence entrepreneurial intentions; also environmental influences and environmental support -support from the peers and family -are a major causative factor behind entrepreneurial intention (Danish & Smith, 2012Sahban, et al, 2014. Hence, perceived social support (PSS) from family and peers has been identified as a having significant influence towards developing or restricting entrepreneurial capability among females, especially at the stage when they are planning or initiating some new business venture (Robb and Coleman, 2010;Molino et al, 2018).…”
Section: Perceived Social Support and E-entrepreneurial Intentionmentioning
confidence: 92%
“…At later stages, social support has been identified as a key factor behind the success of females (Danish & Smith, 2012). Sahban, Kumar and Ramalu (2014) list emotional, esteem, instrumental, informational, and work support as elements of perceived social support (PSS), while family, peergroups, and society as agencies of PSS in their exploratory study. Farooq et al, (2018) and Farrukh et al, (2017) found that PSS has a recognizable influence on entrepreneurial intention and has been reckoned as one of the key indicators for predicting entrepreneurial intentions.…”
Section: Introductionmentioning
confidence: 99%
“…(2005). In this study, the definition of perceived social support from Sahban et al. (2014) is people's beliefs and expectations about advice, guidance, and assistance from social groups.…”
Section: Methodsmentioning
confidence: 99%
“…Sarason et al (1987) defined social support as the intensity of an individual's attachmentbased interactions with friends and family. In general, social support relates to a person's views and expectations concerning the advice, guidance, and assistance obtained from their social group (Sahban et al, 2014), which can increase their self-efficacy. Perceived social support is associated with entrepreneurship, the process through which an entrepreneur captures the significance of social objects, social (human) aspects, and environmental challenges (Mathur and Nihalani, 2012).…”
Section: Gender Stereotype Perception Self-efficacy and Entrepreneuri...mentioning
confidence: 99%